Pengaruh Penggunaan Media Pembelajaran Baamboozle terhadap Hasil Belajar Matematika Kelas IV SD Negeri Ciporos 07 - Ocviani, Ainun Dwi; Kurniawan, Alfi Muklis; Azizah, Amalia Nurul (Indo-MathEdu Intellectuals Journal, 2025)
This study analyzes the effect of using the Baamboozle learning media on the mathematics learning outcomes of grade IV students at SD Negeri Ciporos 07, specifically on the topic of line relationships. The research employed a quantitative method with a Pre-Experimental design using the One Group Pretest-Posttest design on 18 students who were selected purposively. Data were collected through pretest and posttest assessments, observations, and supporting documentation. The instrument was tested for validity and reliability, while the data analysis technique utilized Nonparametric Statistics. Based on the normality test, the data were not normally distributed; therefore, hypothesis testing employed the Wilcoxon Signed Rank Test. The findings show an increase in the students’ average score from 40.20 on the pretest to 67.32 on the posttest after two treatment sessions. Student activity also improved from 76.6% to 86.6%. The Wilcoxon significance value of 0.000 < 0.05 confirms that Baamboozle has a measurable effect. In conclusion, Baamboozle is proven to enhance mathematics learning outcomes and student engagement during the learning process.